Family Christmas at Frances Kamp's San Mateo Home - Watkins, Howard::::::::: (1978)
Marty Hijmans, Gail Graham, Frances Kamp, Cindy the dog; Adam Watkins, Christine Watkins, Howard Watkins, Virginia Graham, Jerry Kamp, Meredith Moran, Greg Graham, Jackie Hijmans Family Christmas photograph